The Meaning of Kāfir in the Quran: A Study of Thematic Interpretation - Ruslan, Ruslan; Khalik, Muh Fihris; Bakri, Mubarak; Maskur, Maskur; Pahrul, Pahrul (Budapest International Research and Critics University, 2022)
This study aims to examine the meaning of the ‘kāfir’ diction in the Quran thematically. The type of research is a literature review with a thematic interpretation approach. Primary data sources consist of the Quran and the book of interpretation (Tafsir Al-Misbah by M. Quraish Shihab and Tafsīr al-Qur’ān al-Aẓim by Ibn Kaṡir). Secondary data sources consist of Arabic dictionaries, books, and journals that discuss the meaning of the ‘kāfir’ diction. Data were collected using documentation techniques and then analyzed using content analysis techniques. The results show that the meaning of the ‘kāfir’ diction in the Quran are (1) denying the existence and oneness of Allah, (2) covering up what is haq (true) or batil (false) and blocking others from Allah, (3) denying to the grace that has been given by Allah, and (4) people who make religion a play. Based on the variety of the ‘kāfir’ diction, it is recommended to Muslim readers not to rush to disbelieve in other Muslims. Because the verdict has social consequences and triggers the birth of a dispute.